Emerald green - Gier, Kerstin (Gier, Kerstin. Liebe geht durch alle Zeiten., 2013)
Since learning she is the Ruby, the final member of the time-traveling Circle of Twelve, nothing has gone right for Gwen and she holds suspicions about both Count Saint-German and Gideon, but as she uncovers the Circle's secrets she finally learns her own destiny.